Consensus on Rehabilitation Guidelines among Orthopedic Surgeons in the United States following Use of Third-Generation Articular Cartilage Repair (MACI) for Treatment of Knee Cartilage Lesions. (December 2021) - Flanigan, David C.; Sherman, Seth L.; Chilelli, Brian; Gersoff, Wayne; Jones, Deryk; Lee, Cassandra A.; Toth, Alison; Cramer, Caryn; Zaporojan, Victor; Carey, James
Objective: The aim of this study was to evaluate levels of consensus in rehabilitation practices following MACI (autologous cultured chondrocytes on porcine collagen membrane) treatment based on the experience of an expert panel of U.S. orthopedic surgeons. Design: A list of 24 questions was devised based on the current MACI rehabilitation protocol, literature review, and discussion with orthopedic surgeons. Known areas of variability were used to establish 4 consensus domains, stratified on lesion location (tibiofemoral [TF] or patellofemoral [PF]), including weightbearing (WB), range of motion (ROM), return to work/daily activities of living, and return to sports. A 3-step Delphi technique was used to establish consensus. Results: Consensus (>75% agreement) was achieved on all 4 consensus domains. Time to full WB was agreed as immediate (with bracing) for PF patients (dependent on concomitant procedures), and 7 to 9 weeks in TF patients. A progression for ROM was agreed that allowed patients to reach 90° by week 4, with subsequent progression as tolerated. The panel estimated that the time to full ROM would be 7 to 9 weeks on average. A range of time was established for release to activities of daily living, work, and sports, dependent on lesion and patient characteristics. Conclusions: Good consensus was established among a panel of U.S. surgeons for rehabilitation practices following MACI treatment of knee cartilage lesions. The consensus of experts can aid surgeons and patients in the expectations and rehabilitation process as MACI surgery becomes more prevalent in the United States.